Between Charybdis and Scylla—an Odyssey in AL amyloidosis: insights and learnings from a narrative review and case report series - Hani Sabbour; Ahmad Alhuraiji; Amr Hanbali; Faraz Khan; Jawahir Alameri; Sultan Alzaher; Dania Mohty; Giovanni Palladini (Therapeutic Advances in Hematology)
Being “between Scylla and Charybdis” is an idiom derived from Greek mythology to mean “between a rock and a hard place” and clinicians managing amyloid light-chain (AL) amyloidosis often find themselves in this predicament. AL amyloidosis is caused by monoclonal light chains, most commonly produced by CD-38 positive plasma cells in target organs. The disease usually involves significant cardiac and/or renal involvement, but the systemic nature of the disease often leads to variable and non-specific manifestations that can critically delay early diagnosis and treatment. Here, we present a case series reflecting primarily the cardiologist and hematologist perspective to uniquely illustrate key learnings that we believe have the potential to improve diagnosis timelines, treatment initiation, and ultimately improve outcomes for this severe disease. Through our case series, we illustrate that to achieve an accurate diagnosis, a high degree of clinical suspicion is needed, and we stress the important requirement of substantial multi-disciplinary collaboration. Our experience strongly indicates that AL amyloidosis patients presenting with cardiac symptoms need to be identified and treated rapidly, prior to the development of irreversible cardiotoxicity. In addition, patients without significant cardiac involvement may benefit from rapid initial treatment with daratumumab along with cyclophosphamide-bortezomib-dexamethasone, which can render patients eligible for autologous stem cell transplant (ASCT) or in some instances means they can forgo ASCT completely. Increased awareness of the disease is needed among general cardiologists and hematologists, and specialized centers with the relevant expertise should be willing to accept patients for fast-track evaluation as part of their standard procedures, due to the unique contribution they can offer in the clinical management of this life-threatening disease.